Trace Element Export From the Critical Zone Triggered by Snowmelt Runoff in a Montane Watershed, Provo River, Utah, USA - Checketts, Hannah N.; Carling, Gregory T.; Fernandez, Diego P.; Nelson, Stephen T.; Rey, Kevin A.; Tingey, David G.; Hale, Colin A.; Packer, Brian N.; Cordner, Cameron P.; Dastrup, Dylan B.; Aanderud, Zachary T. (Frontiers in Water, 2020)
The Critical Zone is an important source of trace elements to headwater streams during the snowmelt runoff period, yet the mechanisms of trace element release are poorly characterized. To evaluate changes in water chemistry in response to snowmelt, we measured trace element and major ion concentrations at three sites in the upper Provo River in northern Utah, USA, over a five–year period spanning years with below– and above–average discharge. We also sampled snowpack, ephemeral streams, and soil water to investigate trace element sources. The river drains siliciclastic bedrock above the upper site, carbonate rocks between the upper and middle sites, and volcanic rocks between the middle and lower sites, with minimal anthropogenic impacts in the watershed. Concentrations of specific trace metals (Be, Al, Cu, and Pb) and rare earth elements (represented by La and Y) increased during snowmelt runoff each year at all three sites, with decreasing concentrations from upstream to downstream. In contrast, major ion concentrations, including Ca2+ and SO42-, were similar year–round at the upper site and were diluted during snowmelt at the lower sites, with increasing concentrations from upstream to downstream. The snowmelt runoff period (April–June) accounted for >84% of the annual trace element loading, with most trace element inputs occurring above the upper sampling site. Concentration–discharge (C–Q) relationships revealed variations in solute behavior from upstream to downstream. For example, at the upstream site the trace elements had a slight positive slope in log C–log Q space, while Ca2+ and SO42- had zero slope. At the downstream sites, the trace elements had a strong positive slope and Ca2+ and SO42- had a negative slope. Trace element concentrations were relatively low in snowpack but elevated in ephemeral streams and soil water, suggesting that flushing of shallow soils by snowmelt causes increased trace element concentrations with positive C–Q relationships in the upper part of the river. Trace element loads propagate downstream where concentrations are diluted by groundwater inputs from carbonate bedrock. Our results demonstrate that soil water flushing in the Critical Zone at the headwaters of mountain streams is an important control on downstream water chemistry.